A New Method to Increase the Spheroidization Rate of Lamellar α Microstructure during Hot Deformation of a Ti–6Al–4V Alloy. Issue 10 (17th June 2020) - Jiang, Yu-Qiang; Lin, Y. C.; Zhao, Chun-Yang; Chen, Ming-Song; He, Dao-Guang
Abstract : Ti–6Al–4V is one of the important materials for manufacturing critical components of aero‐engines. The excellent service properties of aero‐engines are dependent on components and their material microstructures. The spheroidization of a lamellar α microstructure is one of the important methods to refine grains in Ti alloys. Herein, a new method is proposed to increase the spheroidization rate of the lamellar α microstructure during hot deformation of a Ti–6Al–4V alloy. The spheroidization behaviors of the lamellar α microstructure are investigated by one‐pass and two‐pass hot compression tests. A special spheroidization behavior, which is defined as metadynamic spheroidization, is found during inter‐pass; i.e., the lamellar α phase breaks up during the inter‐pass due to the migration and transformation of sub‐boundaries. The spheroidization rate of the lamellar α phase is increased by the metadynamic spheroidization mechanism. The effects of inter‐pass holding time, pre‐strain, and total strain on the spheroidization rate are obvious. Furthermore, the spheroidization rate of lamellar α phases by two‐pass compression is approximately 30% higher than that by one‐pass compression for a given total strain of 1.2. In addition, the strains for the completed spheroidization can be effectively reduced by two‐pass isothermal compression. Abstract : A new method is proposed to increase the spheroidization rate of a lamellar α microstructure during hot deformation of a Ti–6Al–4V alloy. A special spheroidization behavior, which is defined as metadynamic spheroidization, is found during inter‐pass; i.e., the lamellar α phase breaks up during the inter‐pass due to the migration and transformation of sub‐boundaries.